Carex concava (Carex sect. Rhomboidales, Cyperaceae), a new species from Hainan, China - Yang, Hu-Biao; Li, Xiao-Xia; Bai, Chang-Jun; Wang, Wen-Qiang; Liu, Guo-Dao (Phytotaxa, 2016)
A new species of Carex sect. Rhomboidales, Carex concava, is described and illustrated from Hainan, China. The new species is similar to C. paracheniana but differs in having wider blades and longer sheaths of bracts; inflorescence with 3 spikes; terminal spike 2–6 cm long and with a 4–14 cm long peduncle; lateral spikes 3–6 cm long, loosely flowered and with 8–15 cm long peduncles; staminate glume ovate, 1-veined costa excurrent into a shortly awn ca. 0.3 mm; pistillate glume ovate, ca. 4 mm long, 1-veined costa excurrent into a awn ca. 1 mm; perigynia fusiform and green; nutlets inclined-oval, brownish black, with 3 angles deeply constricted at the middle and the side toward of spike-stalk deeply concave at base.